PERKEMBANGAN GERAKAN POLITIK PEREMPUAN DI INDONESIA - Audra Jovani (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2014)
This paper examines the women's movement in Indonesia, during the Japanese occupation, the period after the Proclamation of Independence, a period of Guided Democracy, the New Order Period and the Reform Period. As a social movement that is supported by many people with a clear objective to improve the position and role of women asserting their rights and defending equal political, economic and social rights for women.